Measuring cross‐country material wellbeing and inequality using consumer durables. (19th November 2019) - Grimes, Arthur; Hyland, Sean
Abstract: We measure the mean and inequality in country material wellbeing based on households' consumer durables, using household‐level data from OECD's PISA surveys for 40 countries over 2000–2012. Our consumption‐based measures capture aspects of material wellbeing not captured fully by income‐based measures. For 2012, tests show that the consumption‐based metrics are more closely associated with objective mortality‐related outcomes than are income‐based measures; in 2000 (and over 2000–2012) each set of measures adds information relative to the other. The consumption‐based measures may be particularly useful in revealing where income‐based measures provide inaccurate indications of the mean and/or inequality in household living standards.